The Effect of Emergency Response Training on Flood Disaster Preparedness on Student Council Administrators at SMPN 1 Tibawa - Arifin Umar; Pipin Yunus; Mohammad Ruslan Husain (PROMOTOR, 2024)
The effect of emergency response training on flood disaster preparedness on student council administrators at SMPN 1 TIBAWA. Guided by PIPIN YUNUS as chairman and HASLINDA DAMANSYAH as member Disaster emergency response is a series of activities immediately at the time of a disaster to deal with the adverse effects caused. These activities include pre-disaster, during-disaster, and post-disaster. This study aims to determine the effect of emergency response training on flood disaster preparedness in student council administrators at SMPN 1 TIBAWA. This research method uses a quantitative approach with a type of quasi-experimental research with one group. Samples were taken using total sampling techniques, the number of samples was 36 respondents. Data collection using a questionnaire sheet with data analysis using a Paired T-test with meaning (p-value = 0.05). The results showed that there was an average value of preparedness before 46.61 and preparedness after 73.72 there was an increase of 27.11 preparedness values after being given treatment, then the statistical value was obtained p-value  = 0.00 smaller than 0.05 (p<0.05).  In conclusion, there is an effect of emergency response training on flood disaster preparedness.